The Transcription Factor FoxK Participates with Nup98 To Regulate Antiviral Gene Expression - Debasis Panda (American Society for Microbiology, 2015)
ABSTRACT Upon infection, pathogen recognition leads to a rapidly activated gene expression program that induces antimicrobial effectors to clear the invader. We recently found that Nup98 regulates the expression of a subset of rapidly activated antiviral genes to restrict disparate RNA virus infections in Drosophila by promoting RNA polymerase occupancy at the promoters of these antiviral genes. How Nup98 specifically targets these loci was unclear; however, it is known that Nup98 participates with transcription factors to regulate developmental-gene activation. We reasoned that additional transcription factors may facilitate the Nup98-dependent expression of antiviral genes. In a genome-wide RNA interference (RNAi) screen, we identified a relatively understudied forkhead transcription factor, FoxK, as active against Sindbis virus (SINV) in Drosophila. Here we find that FoxK is active against the panel of viruses that are restricted by Nup98, including SINV and vesicular stomatitis virus (VSV). Mechanistically, we show that FoxK coordinately regulates the Nup98-dependent expression of antiviral genes. Depletion of FoxK significantly reduces Nup98-dependent induction of antiviral genes and reduces the expression of a forkhead response element-containing luciferase reporter. Together, these data show that FoxK-mediated activation of gene expression is Nup98 dependent. We extended our studies to mammalian cells and found that the mammalian ortholog FOXK1 is antiviral against two disparate RNA viruses, SINV and VSV, in human cells. Interestingly, FOXK1 also plays a role in the expression of antiviral genes in mammals: depletion of FOXK1 attenuates virus-inducible interferon-stimulated response element (ISRE) reporter expression. Overall, our results demonstrate a novel role for FOXK1 in regulating the expression of antiviral genes, from insects to humans. IMPORTANCE Innate immunity is characterized by rapid gene expression programs, from insects to mammals. Furthermore, we find that Nup98, known for its roles in the nuclear pore, plays a noncanonical role in binding the promoters and poising a subset of loci for rapid antiviral gene induction. It was unclear how Nup98 accesses these specific genes, and we here demonstrate that Nup98 cooperates with the transcription factor FoxK to regulate this gene expression program. Depletion of FoxK specifically reduces the induction of Nup98-dependent genes. Further, we find that the antiviral function of FoxK is conserved, as the human ortholog FOXK1 is also antiviral and regulates gene expression from virus-induced promoters. Although other forkhead transcription factors have been implicated in immunity, a role for FoxK in antiviral defense was previously unappreciated. Our findings reveal a conserved and novel role for FoxK in coordinating with Nup98 to promote a robust and complex antiviral transcriptional response.